The effects of pegylated interferon/lamivudine therapy on auditory functions in patients with chronic hepatitis B - Karlidag, Gulden Eser; Karlidag, Turgut; Demirdag, Kutbettin; Keles, Erol (Elsevier Sci Ltd, 2011)
Objectives: The aim of this study was to assess the effects of pegylated interferon monotherapy and pegylated interferon + lamivudine combination therapy on auditory functions in patients with chronic hepatitis B (CHB) infection. Methods: A total of 54 patients with a diagnosis of CHB were grouped into four treatment groups: patients in Group 1 received pegylated interferon-alpha 2a; patients in Group 2 received pegylated interferon-alpha 2a + lamivudine; patients in Group 3 received pegylated interferon-alpha 2b, and patients in Group 4 received pegylated interferon-alpha 2b + lamivudine treatment. The auditory system (using standard and high frequency audiometry) and the vestibulocochlear adverse effects including otalgia, tinnitus, vertigo and imbalance were assessed immediately before the onset of the study, and at the 12th, 24th, and 48th weeks of the study. Results: A mean elevation of auditory threshold of 1-10 dB was found in all treatment groups when the thresholds at the onset of the study and the thresholds at the 12th, 24th, and 48th weeks were compared. However, the elevations were not significant. The elevations were mostly at high frequencies (10,000, 12,000 and 16,000 Hz). The most common vestibulocochlear adverse effects related to treatment were tinnitus, vertigo, imbalance, and otalgia, respectively. Tinnitus was the most common adverse effect in Group 2, vertigo was the most common in Group 3, imbalance was at equal frequency in Group 2 and 3, and otalgia was the most common adverse effect in Group 2 (p > 0.05). Conclusion: There were no significant auditory adverse effects in the treatment groups. We think that it may be beneficial to monitor the auditory functions in patients receiving PEG-IFN treatment because of the mild elevation in the auditory thresholds (although not significant). (C) 2010 Elsevier Ireland Ltd. All rights reserved.
Keywords: Chronic hepatitis B; Pegylated interferon; Hearing loss